Case Study : Habib Jewels Sdn. Bhd. / Nurul Aqilah Rosli - Rosli, Nurul Aqilah (2021)
As we can see that wherever we go, people nowadays are wearing accessory such as thejewellery and not only for women but also men are wearing the jewellery. Here, I would like to share about one of the jewellery’s company in Malaysia. Habib Jewels Sdn. Bhd., is one of the most popular company in Malaysia. However, before the name of Habib Jewels, the first company’s name was MA Habib Mohamed. Then the companies change their name to Habib Jewels, ‘Habib’ is inspired from the name of the late founder which is the owner of the companies, Dato’ Haji Habib Mohamed Abdul Latif. In 1958, Habib was began with the late founder Dato’ Haji Habib Mohamed Abdul Latif in Penang. However in nowadays, Habib is fully managed by his son, Dato’ Sri Meer Sadik Habib who is the Executive Chairman of Habib Jewels. Habib is the manufacture and distribute products that based on gold anddiamonds, where the marketed products are jewellery. The Habib Jewel is under the gems and jewellery industry. As we know that Habib Jewels was began at 1958, the period in the world of business is 62 years in total. However Habib Jewels Sdn. Bhd. Was successfully based in the national market in 1998 on the Second Bord of the Kuala Lumpur Stock Exchange and subsequently graduated to Main Board in 2001. Habib Jewels is a successful Chantique holding company, they have been offering customers antique and used jewellery in mint condition. Since the value of their gold product will increase over time, customers will be able to enjoy the benefit from the product when they want to sell them to Habib or other platforms. The motto of Habib Jewels Sdn.Bhd. is The Gift of Happiness. As the successful entrepreneur, there are some personal entrepreneur characteristics of Dato’ Haji Habib Mohamed Abdul Latif. Where he sees and acts on opportunities, persistence person, he also commitment to work contract and last but not least he is using of the influence strategies.